1985
DOI: 10.1152/ajpheart.1985.249.6.h1106
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of lung vascular resistance after chronic systemic-to-pulmonary shunts

Abstract: Congenital cardiac shunts produce pathological lesions on the arterial side of the lung vasculature. We examined the effects of chronic shunts (14.2 +/- 1.2 mo) in 10 young dogs, between the left subclavian and the left lower lobe (LLL) artery, on pulmonary vascular pressure and flow (P-Q) relationships, segmental resistance with arterial and venous occlusion (AVO), and sensitivity to drugs. At final thoracotomy, mean LLL pulmonary arterial pressure (Ppa) was 23.2 +/- 4.3 mmHg compared with 11.9 +/- 0.9 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Medical conditions with shunting of blood from the left to the right side of the heart and increased cardiac output and pulmonary blood flow, such as congenital heart disease, are well recognized as possible causes of PH. 5,6 Excess mortality rates due to cardiovascular disease in end-stage renal disease (ESRD) patients had been described by epidemiological and clinical studies. It accounts for approximately 50 percent of deaths in dialysis patients.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…Medical conditions with shunting of blood from the left to the right side of the heart and increased cardiac output and pulmonary blood flow, such as congenital heart disease, are well recognized as possible causes of PH. 5,6 Excess mortality rates due to cardiovascular disease in end-stage renal disease (ESRD) patients had been described by epidemiological and clinical studies. It accounts for approximately 50 percent of deaths in dialysis patients.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…Both the pulmonary venous and arterial systems are well known to be interrelated (10 -13). It has been shown that sudden occlusion of a pulmonary vein is soon followed by gradual decline and then cessation of the arterial flow to the affected segment (12,14). This is caused by a decline in the arteriovenous gradient as well as compression by the developing tissue edema (10).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the involved alveoli are affected by the resulting ischemia and surrounding edema, leading to atelectasis, infarction, or susceptibility to infections (15). With the resulting alterations in pulmonary hemodynamics, redistribution of blood flow occurs with opening of vascular channels or neovascularization in which tissue hypoxia is known to play a role (12,14). Hence, the venous drainage of the affected segment becomes mainly dependent on the ipsilateral veins draining the healthy lobes.…”
Section: Discussionmentioning
confidence: 99%
“…The major mechanisms for the development of PH are an increase in pulmonary BFR and pulmonary vascular resistance [13,14]. Both mechanisms are involved in patients with chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%